Chemical and sensory quality changes in fish balls prepared from Alburnus mossulensis Heckel, 1843 during frozen storage - Duman, M.; Peksezer, B. (Wiley-Blackwell, 2016)
The effects of frozen storage on fish balls derived from Alburnus mossulensis at -18 +/- 2 degrees C were studied. Several chemical parameters were determined [pH, total volatile basic nitrogen (TVB-N), thiobarbituric acid (TBA), free fatty acids (FFA)]. Further, microbiological effects were analysed during storage [Total mesophilic aerobic bacteria (TMAB), total psychrophilic bacteria (TPB), coliform and yeast-mould count]. Finally, sensory quality tests were performed with fresh and stored balls. Fish balls were composed of 64% fish meat and 36% other ingredients, including: 18% boiled rice, 11.4% onions, 1.8% parsley, 3.8% fat, 0.7% salt and 0.26% black pepper. This basic mixture was processed to form small (25 g) balls and a pre-cooking process was applied. Test balls were divided into two groups: vacuum packed (A1) and a control group without vacuum (A2). Test packages were stored for 6 months, resulting in increased pH, TVB-N, TBA and FFA, while the values for sensory properties declined. However, these changes did not drop below the limit of acceptance. Total mesophilic aerobic bacteria and total psychrophilic bacteria were significantly reduced in both A1 and A2 groups.
1st International Fisheries Symposium -- MAR 24-27, 2013 -- Girne, CYPRUS
Keywords: Rosemary Extract; Burgers; -18-Degrees-C; Fingers